Data quality review during prenatal care - Silvânia Maria Mendes Vasconcelos; Lucilane Maria Sales da Silva; Rita Neuma Dantas Cavalcante de Abreu; Eliane Magalhães de Brito; Thereza Maria Magalhães Moreira; Alison Alves de Farias (Revista Brasileira em Promoção da Saúde, 2009)
Aim: To review the quality of prenatal care data registered by the professionals from the Family Health Strategy (ESF) in Jericoacoara city – Ceara State – Brazil. Methods: This was a quantitative and documental study, in which were analyzed 71 obstetric records of pregnant women who underwent prenatal care in 2006. The studied variables comprised those obtained by data quality review of standard obstetric records regarding to socioeconomic aspects, family history, personal and obstetric and the data related to current pregnancy. Results: Among the 71 obstetric records reviewed, in 70 of them (98.6%), the socioeconomic data were completed satisfactorily. The data concerning the history of familiar and personal morbidity, besides obstetric and gynecological history of the pregnant women were 100% (71) complete. Referring to the data of current pregnancy collected during the anamnesis of the first medical appointment, it was detected that 47 (66.2%) were filled in properly, while in 24 (33.8%) of them there were missing important data, such as height and weight of the pregnant women. From all obstetric records, in only 60 (84.5%) there were the registers of all laboratory tests compulsory for the first trimester of pregnancy and it’s highlighted that only 43 (60.6%) of the records were filled in properly regarding the lab tests of the third trimester. It was yet verified that in only 6 (8.5%) of the records there was information related to the curve of uterine height/gestational age. Conclusion: In this study, the adequate filling of obstetric records was observed, although we found a great number of lack or of incomplete registers in the topic related to the graphs of height/weight and the curve of uterine height/ gestational age.